Bioremediation via Methanotrophy: Overview of Recent Findings and Suggestions for Future Research - Semrau, Jeremy (Frontiers in Microbiology, 2011)
Microbially-mediated bioremediation of polluted sites has been a subject of much research over the past 30 years, with many different compounds shown to be degraded under both aerobic and anaerobic conditions. Aerobic-mediated bioremediation commonly examines the use of methanotrophs, microorganisms that consume methane as their sole source of carbon and energy. Given the diverse environments in which methanotrophs have been found, the range of substrates they can degrade and the fact that they can be easily stimulated with the provision of methane and oxygen, these microorganisms in particular have been examined for aerobic degradation of chlorinated hydrocarbons. The physiological and phylogenetic diversity of methanotrophy, however, has increased substantially in just the past five years. Here in this review, the current state of knowledge of methanotrophy, particularly as it applies to pollutant degradation is summarized, and suggestions for future research provided.